STRUKTUR KOMUNITAS ANNELIDA SEBAGAI BIOINDIKATOR PENCEMARAN SUNGAI ANCAR KOTA MATARAM - Iwan Doddy Dharmawibawa (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2019)
Ancar River is a river that is used by many residents for various activities, such as agricultural activities, fisheries, and planting water spinach. In addition to these activities, the Ancar River is also used as a place for domestic waste disposal and disposal of the tofu waste industry so that it can have a negative impact on water resources, including causing a decrease in water quality. The Annelida response to environmental changes can be used to see the effect of various activities, such as the impact of industrial activities, agriculture, and land use. This study aims to assess the community structure of Annelida as bioindicators of the waters against the content of polluted material found in the Ancar River. This research is descriptive explorative, using quantitative and qualitative approaches. This study uses the